Estudo da adição de rejeito de minério de ferro para produção de compósitos cimentícios de alto desempenho - Abner Araújo Fajardo (2023)
Iron ore is of great importance to Brazil, being the second largest producing country in the world. However, mining generates a high volume of waste, causing great risks to the local population and also various environmental impacts. Therefore, the civil construction sector presents itself as an alternative for the disposal of Iron Ore Tailings (Iron Ore Tailings - IOT), which can reduce socio-economic and environmental impacts. Because of this, this work aims to produce high-performance structural mortars, using mineral admixture from raw iron mining tailings, adopting the concepts of particle packaging. Analyze the hydrated compounds, their mechanical properties and durability indicators over time, at 7, 28 and 112 days. Material characterization analyzes were carried out, namely: chemical composition, physical and mineralogical characteristics. Mechanical properties, durability indicators and hydrated compounds were studied. The fine grain size of the waste was found to be 4.7 µm; its surface area of 35.133 m²/g; its density is 3.85 g/cm³; its chemical composition of 48% Fe2O3 and 21.20% SiO2. For the age of 112 days, the iron ore tailing mortar obtained the following results: porosity 1.64%; 1.51% quantitative porosity through SEM image analysis; 0.68% water absorption by immersion; 0.04% of the capillarity coefficient; 95.42 MPa for compressive strength; 8.26 MPa for flexural tensile strength; 833 kΩ.cm in surface electrical resistivity; 1,973 Ω.m. for volumetric electrical resistivity; 1.38mg of calcium hydroxide mass loss; 1.32 mg of calcium carbonate mass loss. Therefore, over time, iron ore waste mortar has tended to improve its mechanical properties and durability indicators. It can be used as a mineral admixture, through particle packaging to produce high structural performance mortar.